(untitled) - Trimmer, Christian; Juanita, Kaylani (New York, NY, 2021)
A little girl's small act of kindness after a storm spreads throughout her town so that the next time there is a storm, her community comes together to make a big difference.
Keywords: Community life; Fiction; Starfishes; Storms; Storms; Fiction; Fiction; Fiction; Juvenile fiction; Juvenile fiction; Starfishes; Juvenile fiction; Community life; Juvenile fiction; Kindness; Kindness; Picture books